A Study of Multivariate Modalities of Therapy in Gall Bladder Malignancies with Different Clinical, Radiological and Histo-Pathological Profiles at a Low Resource Indian Cancer Centre - Singh, Taruna; Verma, Yogesh; Tiwari, Meena; Hadi, Rahat; Singh, Mukti Nath (Asian Pacific Journal of Cancer Care, 2022)
Introduction: The effectiveness of adjuvant radiation therapy (RT) in the treatment of GBC has not yet been established. The effectiveness of adjuvant radiation therapy (RT) in the treatment of GBC has not yet been established. Following surgical resection, postoperative external beam RT can diminish local relapse; though effect on global survival has not been confirmed due to lack of good quality clinical trials. Thus the aim of the study was to assess the efficacy of the multivariate modality of therapy in Gallbladder malignancies. Materials and method: The present prospective comparative study of multivariate modality of therapy in Gallbladder malignancies was carried out in a low resource North Indian cancer center from. Only those patients were selected who were histologically confirmed of adenocarconima of gall bladder, squamous cell carcinoma and oat cell carcinoma. Staging was done according to TNM classification no concurrent medical illness, Karnofsky performances status of patient >70. Statistical analyses were performed using SPSS version 23.0 (SPSS Inc., Chicago, IL, USA). A value of p<0.05 was considered statistically significant. Result: Majority (29.3%) of the cases were aged 61-70 years just followed by the age group 41-50 years, females were in majority (73.2%). Higher stage had significantly higher risk of partial or no response (p<0.001). An increasing trend of toxicities was observed with increasing dose. Significant association was found between toxicities and treatment response at dose 2000 cGy (p<0.001) and 4500 cGy (p<0.001). The Cox regression analysis showed higher hazard ratio for stage IV (HR=2.33 95% CI : 0.31-17.66) followed by stage II/III (HR=1.67 95% CI : 0.17-16.02). Conclusion: Healthcare professionals should discuss the indeterminate benefit and possible risks of adjuvant therapy when counseling their patients and reassure enrollment in clinical trials of novel regimens. The curative potential of current adjuvant therapy in gallbladder cancer is questionable, justifying placebo-controlled investigation of novel chemotherapy combinations or alternative approaches. To confirm the efficacy of adjuvant therapy, a major randomized controlled trial is required with large sample size. The improvement in radiation delivery with intensity modulated radiotherapy (IMRT), image guided radiotherapy has further paved the way for exploration of adjuvant radiation for GBC.